On Volterra inequalities and their applications. (22nd January 2004) - Hącia, Lechosław
Abstract : We present certain variants of two-dimensional andn -dimensional Volterra integral inequalities. In particular, generalizations of the Gronwall inequality are obtained. These results are applied in various problems for differential and integral equations.